Curva de crescimento e valor nutritivo do capim-elefante (Pennisetum purpureum Schum) "A-146 Taiwan" - F Andrade , Ivo; Alberto Gomide, José (Revista Ceres, 2025)
An experiment was carried out atthe Federal University of Viçosa, to establish the growth curve of elephantgrass (Taiwan A-146) and to study the changes in nutritive value of the grass and the vigor of the regrowth when harvested at various ages. Harvests were made at 28, 56, 84, 112, 140, 168 and 196 days of age after a general cutting taken onJanuary 15, 1969. The experimental design was a randomized complete block design having 5 replications.